Effects of Diabetic Complications on Health-Related Quality of Life Impairment in Vietnamese Patients with Type 2 Diabetes - Tuyen Ba Pham; Trung Thanh Nguyen; Huyen Thi Truong; Chin Huu Trinh; Ha Ngoc Thi Du; Tam Thi Ngo; Long Hoang Nguyen (Journal of Diabetes Research, 2020)
Complications of type 2 diabetes mellitus (T2DM) adversely influence patients’ health-related quality of life (HRQOL). This study is aimed at examining HRQOL of T2DM patients, as well as the effects of diabetic complications and comorbidities on HRQOL in this population. This was a hospital-based cross-sectional study on 214 T2DM patients in Hanoi, Vietnam. Short-form 12 version 2 (SF-12v2) and EuroQOL-5 Dimensions-5 Levels (EQ-5D-5L) were employed to measure the HRQOL. The median physical component summary score (PCS), mental component summary score (MCS), and EQ-5D index were 45.6, 56.3, and 0.94, respectively. Having at least one diabetic complication was associated with the reduction of SF-12 scores in social functioning (Diff.=−5.69, 95%CI=−9.24; -2.13), role emotional (Diff.=−1.81, 95%CI=−3.12; -0.51), and MCS (Diff.=−2.55, 95%CI=−5.01; -0.1). Significant decrement of physical functioning, role physical, social functioning, role emotional, and MCS was found in patients having diabetic heart diseases compared to those without diabetic complications. The study revealed that HRQOL of Vietnamese patients with diabetic complications was moderately low, especially in social and mental health perspectives. Strategies to prevent the onset of diabetic complications should be developed as a priority in diabetes management.